Institutions and preferences determine resilience of ecological-economic systems - Quaas, Martin F.; Baumgärtner, Stefan; Derissen, Sandra; Strunz, Sebastian (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
We perform a model analysis to study the origins of limited resilience in ecological-economic systems. We demonstrate that the resilience properties of the ecosystem are essentially determined by the management institutions and consumers’ preferences for ecosystem services. In particular, we show that complementarity of ecosystem services in human well-being and open access of the ecosystem to profit-maximizing harvesting firms may lead to limited resilience of the ecosystem. We conclude that the role of human preferences and management institutions is not just to facilitate adaptation to, or transformation of, some natural dynamics of ecosystems. Rather, human preferences and management institutions are themselves important determinants of the fundamental dynamic characteristics of the ecological-economic system, such as limited resilience.
Keywords: Ecological-Economic System; Natural Resource Management; Resilience; 330 Wirtschaft